Application of FEM and SEA in predicting vibro-acoustic behavior of a flat ribbed panel structure - Madjlesi, Reza (Canadian Acoustics, 2007)
Two major design tools in predicting acoustical response of the coupled structure-cavity are presented. The response of a structure excited by a point force is predicted using Finite element method (FEM) and statistical energy analysis (SEA). Structural testing was required to confirm integrity of the FE model of the structure, and modal testing was performed on the ribbed panel. The ribbed panel structure was modeled with 9600 Quad8 shell elements, and the cavity inside the box was modeled with 31000 Hexa8 solid elements. The modal response of the structure, for FE model, is used for structural correlation, and fine FRF measurement was performed on the suspended ribbed panel. FE modeling is used to predict the response of the system for low-mid frequency range. Predicted average interior noise of the box-ribbed panel system when excited by a point force, where FE predictions correlate well with the measured sound pressure level for frequency range of 200-1000 Hz.